KEMAMPUAN MENGUBAH TEKS WAWANCARA MENJADI KARANGAN NARASI SISWA KELAS VII SMP NEGERI 2 LEMBAH MELINTANG KABUPATEN PASAMAN BARAT - Huda, Ihsainil; Bahardur, Iswadi; Afrinda, Putri Dian (Pendidikan Bahasa Indonesia, 2013)
The problem in this research are first, the students competence was low in writing narrative text. Second, the student difficult to make differences between narrative and other kond of writing. Third, learning techniques that can motivateÂ students in write narrative essay is not used by teacher. The purpose of this research is to describe the ability to change interview text into narrative essayÂ for grade VII of SMP Negeri 2 Lembah Melintang Kabupaten Pasaman Barat. The kind of this research is quantitative with descriptive menthod. The kind of this research is students grade VII at SMP Negeri 2 Lembah Melintang Kabupaten Pasaman Barat 27 students. Sample of this research is students grade VII sampling techniques is purposional random sampling. The instrument of the research use performance test.Based on the data analysis, it can be seen the ability of students to change interview text into narrative essay students grade VII SMP Negeri 2 Lembah Melintang Kabupaten Pasaman Barat considered more than enaught (LDC) with an average of students mastery 72,13%. Next, the comperence to change interview into narrative essay for students grade VII SMP Negeri 2 Lembah Melintang Kabupaten Pasaman Barat for (1) flow relatively more than enough (LDC) with an average of 70.36%, (2) punctuation point quite well once (BS) with an average of 93.82%, punctuation, comma belong either once (BS) with an average of 87.65%, relatively less punctuation quotation once (KS) with an average of 34.56, (Ldc) with an average of 67.90%, (3) characters and events perfectly classified (S) with an average of 100%, (4) the sentence is not directly considered less (K) with an average of 43.20%.